KAJIAN AKUNTABILITAS KINERJA PEMERINTAH KECAMATAN TOULUAAN KABUPATEN MINAHASA TENGGARA - RINI SUTRIKA SUOTH; Jantje Mandey; Sonny Rompas (Universitas Sam Ratulangi, 2014)
Accountability of government agency performance embodies an obligation to account for thesuccess or failure of the implementation of policies, programs and activities to stakeholders or general public.In fact, performance accountability can not be optimally realized by many government agencies. From thesestudies were conducted to determine how government performance accountability at Touluaan district ofSoutheast Minahasa regency. Based on a literature review of the criteria used effectiveness, efficiency,responsiveness, and transparency to look government performance accountability at Touluaan districtThe research used a qualitative method. Key informants in this study were officers / employees ofthe sub-district 3 and 2 personnel section chief executive staff; and 2 village officials and 3 leaders /community leaders, so that the total number of informants there are 12 people. The research instrument was aresearcher himself, while gathering data using interview techniques. Method analysis was performed withqualitative analysis techniques interactive model of Miles and Hubernann.The results of analysis indicate effectiveness, efficiency, responsiveness, and transparency in theimplementation of the program / activity generally show a fairly good quality. It was concluded that thegovernment performance accountability Touluaan district seen from the aspect of effectiveness, efficiency,responsiveness, and transparancy has shown a fairly good level of achievement. To improve the performanceof government accountability Touluaan districts it is necessary to increase the number of employees,improving the quality of human resources personnel, increased budgetary allocations, and additional meansof employment.Keywords: performance accountability.